Physicochemical, sensorial and antioxidant properties of sardine fish patties incorporated with different natural additives - Chong, Chi-Cheng; Muhamad Faris Ab Aziz,; Mohammad Rashedi Ismail-Fitry, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Sardine fish patty is a processed seafood product that easily spoiled because of oxidation. Oregano, cloves, cinnamon, turmeric, and green tea contain antioxidant properties that could preserve the fish patty. This study aimed to incorporate these ingredients into sardine fish patties and investigate their effects on the physicochemical properties, sensory evaluation, and lipid oxidation of the patties. The fresh sardine patties were treated with 0.5% of oregano (PWO), cloves (PWC), cinnamon (PWCI), turmeric (PWT) or green tea (PWGT) before being cooked, cooled and chill-stored for 12 days. No significant effects of the treatments were observed on moisture content, cooking yield, and shrinkage of the patties. The incorporation of turmeric significantly (P<0.05) affected all colour parameters on the patties (PWT). Although PWGT showed slightly increased values in some texture profiling parameters, the PWGT also showed positive acceptability regarding sensory evaluation for most of the eating quality parameters. A significant (P<0.05) reduction in TBARS values in the patties incorporated with green tea (PWGT), while increased scavenging activity values of the PWGT and cloves (PWC) were observed. Thus, the study implied that green tea demonstrated a good effect on sardine fish patty, as compared to spices, which could be a potential natural preservative to preserve the fish product during storage.